Peningkatan Keterampilan Membaca Puisi Siswa Kelas Iv Dengan Menggunakan Video Pembelajaran Di Sd Negeri I Nagrikidul - Ramadan, Pirman Yusup; Iskandar, Sofyan; Sari, Nadia Tiara Antik (Peneliti.net, 2023)
The background of this study is the lack of ability of four-grade students in SD Negeri 1 Nagri Kidul in poetry reading skills. Students who are not excessively involved in class, teachers using a traditional teaching method, and no learning media tools can be used. Therefore, using the method of Classroom Action Research aims to overcome the problems that occur in four grade students. The result of this study indicates that students increased their scores in each cycle. In the first cycle, the average score of students for reading poetry is 66, and in the second cycle is 80. It means that using video learning media can improve the poetry reading skills of four-grade students in SD Negeri 1 Nagri Kidul. Based on the result of this study, it also showed an increase in student activity in cycle one and got good criteria; in cycle two, they got excellent criteria. Also, the observations of the teachers increased in every process. This study shows that using a video learning media can improve the poetry reading skills of four-grade students in SD Negeri 1 Nagri Kidul. As a consequence, it is expected that it can be used as material for reference and advice for teachers, specifically in reading poetry classes that learning video media can be developed and operated since it makes student improve their skills in reading a poetry.